Experimental investigation on corrosion behavior of friction stir welded AA7075-T651 aluminium alloy under 3.5% wt NaCl environment. (2021) - Prabhuraj, P.; Rajakumar, S.
Abstract: The corrosion resistance of high strength heat treatable aluminium alloy is able to form an oxide film on its surface. In aggressive corrosion media, the oxide film can undergo corrosion responses in chloride-containing environments. The welding of AA7075 is important for advanced structural application in aircraft and automotive industries. Friction Stir Welding (FSW) method is the new technique and a sound welding method in the aluminium industry, which overcomes solidification cracking problem compared to the conventional fusion welding technique. Rolled plates of 10 mm thickness of AA7075-T651 were butt welded by using FSW process. The corrosion surface morphology and behaviour were investigated by conducting a salt fog test in sodium chloride solution at various spraying time, chloride ion and pH value. An objective was initiated to extend an experimental relationship to predict the corrosion rate of stir zone of FSW AA7075-T651 joints. Three factors five levels of a centre rotatable matrix was used to reduce the number of experimental circumstances and response surface methodology was used to develop an empirical relationship between salt fog variables. The empirical model can be used to predict the corrosion rate of FSW AA7075-T651 joints.